Penumbuhan Bakat Melalui Pembelajaran Tari Bagi Anak-anak di Sonorejo Kabupaten Sukoharjo - Mamik Suharti (Institut Seni Indonesia Surakarta, 2010)
The dance lessons that take place outside school hours for children in the Sonorejo area are a special kind of activity or service which aims to develop the children’s talent in the field of dance from an early age. Children from kindergarten up to high school age take part in the dance lessons. So far, the process has had encouraging results both in terms of quantity and quality, and the children have acquired a broad range of dance skills. Since the children come from a variety of different backgrounds and are of varying ages and from several different villages, the lessons implement a teaching model known as Magnet School and Investigation, while the method used is that of drills, lectures, and play. With this approach, the dance lessons seem to run well. As a result of the dance lessons, every child is able to participate in a concert by memorizing and enjoying the dances they have learned. Hence, in addition to developing children’s dance skills from a young age, they are also able to show their appreciation which in the future will be beneficial to their studies as well as contributing to the preservation and development of the art of dance in the future.Keywords : lessons, dance, and students